2008
DOI: 10.1021/jm800888q
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Active Aldosterone Synthase Inhibitors with Improved Selectivity: Lead Optimization Providing a Series of Pyridine Substituted 3,4-Dihydro-1H-quinolin-2-one Derivatives

Abstract: Pyridine substituted naphthalenes (e.g., I-III) constitute a class of potent inhibitors of aldosterone synthase (CYP11B2). To overcome the unwanted inhibition of the hepatic enzyme CYP1A2, we aimed at reducing the number of aromatic carbons of these molecules because aromaticity has previously been identified to correlate positively with CYP1A2 inhibition. As hypothesized, inhibitors with a tetrahydronaphthalene type molecular scaffold (1-11) exhibit a decreased CYP1A2 inhibition. However, tetralone 9 turned o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
61
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 53 publications
1
61
0
Order By: Relevance
“…naphthalenes, [30] dihydronaphthalenes [31] and dihydroquinolinones. [34] In this study, all 4-isoquinoline substituted compounds also show stronger hCYP11B2 inhibitory activity than the parent pyridine compounds. Thus, it can be concluded that substitution of the pyridine by isoquinoline as heme-complexing group leads to a considerable improvement in hCYP11B2 inhibition without affecting selectivity toward hCYP11B1.…”
Section: Discussionmentioning
confidence: 53%
See 4 more Smart Citations
“…naphthalenes, [30] dihydronaphthalenes [31] and dihydroquinolinones. [34] In this study, all 4-isoquinoline substituted compounds also show stronger hCYP11B2 inhibitory activity than the parent pyridine compounds. Thus, it can be concluded that substitution of the pyridine by isoquinoline as heme-complexing group leads to a considerable improvement in hCYP11B2 inhibition without affecting selectivity toward hCYP11B1.…”
Section: Discussionmentioning
confidence: 53%
“…[34] Further modifications in this compound class were performed in this study in order to find new compounds suitable for in vivo tests in the rat.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations